Ventanillas de Salud: A Collaborative and Binational Health Access and Preventive Care Program - Maria Gudelia Rangel Gomez; Josana Tonda; G. Rogelio Zapata; Michael Flynn; Francesca Gany; Juanita Lara; Ilan Shapiro; Cecilia Ballesteros Rosales (Frontiers Media S.A., 2017)
While individuals of Mexican origin are the largest immigrant group living in the U.S., this population is also the highest uninsured. Health disparities related to access to health care, among other social determinants, continue to be a challenge for this population. The government of Mexico, in an effort to address these disparities and improve the quality of life of citizens living abroad, has partnered with governmental and non-governmental health-care organizations in the U.S. by developing and implementing an initiative known as Ventanillas de Salud-Health Windows-(VDS). The VDS is located throughout the Mexican Consular network and aim to increase access to health care and health literacy, provide health screenings, and promote healthy lifestyle choices among low-income and immigrant Mexican populations in the U.S.